Assume that the function f is a one-to-one function If f(6)=4, find f^−1(4). and The same thing but when given the inverse: If f^−1(−2)=−5, find f(−5).
Follow Math Help Forum on Facebook and Google+
Originally Posted by Lolcats Assume that the function f is a one-to-one function If f(6)=4, find f^−1(4). and The same thing but when given the inverse: If f^−1(−2)=−5, find f(−5). Since the function is injective it has a left-inverse. Thus we have that .
Originally Posted by Lolcats Assume that the function f is a one-to-one function If f(6)=4, find f^−1(4). and The same thing but when given the inverse: If f^−1(−2)=−5, find f(−5). Use the definition of "inverse function", of course! That is, if y= f(x) , then . If , that is, x= 6 and y= 4, . Of course, if then y= f(x) so the other should be easy now.
Thank you! That makes alot of sense!
View Tag Cloud